1988
DOI: 10.1159/000132677
|View full text |Cite
|
Sign up to set email alerts
|

Fragile sites, telomeric DNA sequences, B chromosomes, and DNA content in raccoon dogs, <i>Nyctereutes procyonoides, </i>with comparative notes on foxes, coyote, wolf, and raccoon

Abstract: Earlier studies of the genus Nyctereutes disclosed two subspecies of differing chromosome numbers accompanied by B chromosomes. To further define the relationship of these subspecies to each other, and to other carnivores, and to learn more about the structure and function of their chromosomes, we charcterized and compared the genomes in terms of DNA content by flow cytometry, fragile sites induced by aphidicolin, and telomere sequences using biotinylated DNA probes detected with fluorescence. We also characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 8 publications
4
48
0
1
Order By: Relevance
“…B chromosomes do not pair with any of the standard A chromosomes during meiosis and have irregular modes of inheritance. At the DNA level, B chromosomes are usually enriched in tandem repeated sequences (Potapov et al, 1990), long interspersed nuclear elements, short interspersed nuclear elements (Peppers et al, 1997), interstitial telomeric sequences (Wurster-Hill et al, 1988), ribosomal DNA (rDNA) clusters (Stitou et al, 2000;Szczerbal and Switonski, 2003), and others. In some species, rDNA genes located on the B chromosomes have been demonstrated to exhibit transcriptional activity (Leach et al, 2005;Ruiz-Estevez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…B chromosomes do not pair with any of the standard A chromosomes during meiosis and have irregular modes of inheritance. At the DNA level, B chromosomes are usually enriched in tandem repeated sequences (Potapov et al, 1990), long interspersed nuclear elements, short interspersed nuclear elements (Peppers et al, 1997), interstitial telomeric sequences (Wurster-Hill et al, 1988), ribosomal DNA (rDNA) clusters (Stitou et al, 2000;Szczerbal and Switonski, 2003), and others. In some species, rDNA genes located on the B chromosomes have been demonstrated to exhibit transcriptional activity (Leach et al, 2005;Ruiz-Estevez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Study on the molecular nature of the B chromosomes, performed by the FISH technique with the use of the telomeric DNA probe, revealed the presence of these sequences throughout the length of the B chromosomes in both subspecies of the raccoon dog (WURSTER-HILL et al 1988). Recently, B chromosomes of the Japanese raccoon dog were studied by the chromosome painting approach.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was suggested that in both subspecies of the raccoon dog the Bs are rich in telomeric or telomeric-like sequences. In the same study it was shown that the Bs in the red fox have only typical distal signals while hybridised with the telomeric probe ( WURSTER-HILL et al 1988). The use of the rDNA probe (genes coding rRNA genes) onto the Chinese raccoon dog chromosomes showed hybridisation also on a large segment of the Bs, apart from terminal signals on three autosome pairs and the Y chromosome, which are known to carry active NORs (nucleolar organizer regions).…”
Section: Nature Of the B Chromosomesmentioning
confidence: 90%